Dynamic System for Analyzing the Effect of Growth (Government Spending, Population, Wages) and (Alk and Kor (Technology)) on Economic Growth - Rahmawati, Deti (Indonesian Journal of Development Studies, 2022)
Indonesia's Economic Improvement After the Covid Pandemic, economic growth will be influenced by various factors. This study tries to analyze the Growth Modeling (Government Spending, Population, Wages) and (Alk and Kor (Technology)) of the economy needed to be able to analyze its effect on economic growth. This study used dynamic system modeling using Vensim. This growth is a form of economic growth that will have an effect on job creation and it will have a major effect on the unemployment rate. The results of the first simulation show that labor needs will be influenced by real wage or real wages, then by Short run Expected Demand, and Alfa. While the Alpha Forming Elements themselves are KOR (Capital Output Ratio), Life Of capital (ALK) and Real Interest Rate. The results of Simulation 2 show that the increasing economy will also increase the number of workers and capital, but that does not reduce unemployment. This is because the state of the kor and alk is considered constant. Furthermore, it will be tested in the next simulation when the alk dank or is not considered constant. The results of Simulation 3 ALK that continue to rise or in other senses the depreciation is getting bigger, it can reduce the level of upgrading, because the speed of innovation and technology makes companies have to make new machines quickly.